What is the Social Innovation Community? Conceptualizing an Emergent Collaborative Organization. Issue 1 (2nd January 2016) - Toivonen, Tuukka
Abstract: Although social innovation is stimulating tremendous interest among scholars and policy-makers, its emergent catalysts are insufficiently understood. This paper thus identifies and explores a relevant collaborative organization, the social innovation community (SIC). Found in cosmopolitan cities, SICs are held together by recognizable shared cultures and online/offline spaces. This account sets out a basic categorization of SICs, profiles their salient features, and offers an original definition. SICs support early-stage social entrepreneurship but may also help to introduce social innovation into new cultural settings, re-programme wider innovation circuits, and promote productive collaboration amid diversity.